Conceptualisation of hydrogeological system in the crystalline aquifer of the Hout River Catchment, Limpopo Province - Tshipala, Despina (My University, 2018)
The research focused on conceptualisation of a hydrogeological system in the Hout River Catchment, Limpopo Province. The hydrogeological system in this area is characterised by crystalline aquifer within the Hout-Goudplaats Granite Gneiss, greenstone remnants and younger granite plutons. Like other semi-arid environment, groundwater is the main source of water for agricultural activities and livelihoods. However, normal annual rainfall seems to be insignificant to the overall aquifer replenishment. Aquifer replenishment in these settings has been associated with major rainfall events. The main objective of this study was to develop a feasible hydrogeological model to represent recharge estimation rates and sources, groundwater flow and occurrence and anthropogenic influence within the catchment. The structural and geophysical analyses showed that dominant dolerite dykes and other lineaments trends are in the NE and NW directions and the measured dolerite dykes have strikes ranging between 088o and 075o and dip angle between 50o and 55o. The lineaments and mafic dykes are highly fractured and weathered. Some of these structures are magnetic and some are non-magnetic. Groundwater levels distribution suggest high levels related to lineaments and dykes, thus indicating structures allowing groundwater flow. There is no clear correlation between structural orientation and physicochemical parameters distribution. Groundwater with high TDS and EC are related to deeply weathered and fractured parts of the aquifer like the Mogwadi area. This groundwater will be less palatable if calcium and magnesium form large constituents of the TDS. Towards the surface headwaters of the Hout River, groundwater shows low TDS and EC. The highest observed mean annual rainfall for the years analysed in this study is 335.02 mm. The catchment is largely receiving rainfall from a regional moisture source shown by lower average deuterium excess of 2.77 ‰. This shows that very little rainfall is recharging the aquifer and the overall aquifer replenishment occurred during humid colder climates from a regional source of moisture possibly the Indian Ocean. The highest mean annual groundwater recharge rate estimated using WTF method is 39.33% of the MAP. The surface water runoff is 13.38% of the MAP. In 2015, groundwater abstractions were estimated at 25.501 Mm3. The 14C activity for the groundwater samples is highest in the north-western part of the catchment at 100 pMC and decreases towards the southern and southern-east part of the catchment at a range between 84.3 to 87.7 pMC. The radiogenic isotopes have shown that older groundwater occurs in pockets of identified weathered and deep fractured iii Goudplaats-Hout River Gneiss areas. In contrast, a spring along the northern part of the catchment has a 3H value of 2.2 TU, which shows recharge that occurred 4 years ago. The TDS and EC of this spring water are also low showing less mineralised and dissolved solids; there was no barium-carbonate precipitate formed during sampling of radiogenic carbon, which is indicative of abundant bicarbonate and hence availability of meteoric water. Groundwater sources are emerging from the northern, southern and north-western part of the catchment. Based on 3H and 14C, there are two aquifers within the catchment, which shows interconnectedness along the northern part of the catchment and more disconnected towards the south-eastern part of the catchment.
A research report submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Hydrogeology School of Geo-sciences, October 2018
Keywords: Groundwater--South Africa; Aquifers--South Africa; Groundwater flow--South Africa